Aposynag?gos and the Historical Jesus in John : Rethinking the Historicity of the Johannine Expulsion Passages. - Bernier, Jonathan (Brill, 2013)
In Aposynag?gos and the Historical Jesus in John, Bernier argues that the Johannine expulsion passages could plausibly describe events that occurred during Jesus' lifetime.